Pengembangan Bahan Ajar Berbasis Universal Design For Learning Untuk Pendidikan Inklusif Sekolah Dasar: A Systematic Literature Review - Atikah Atikah; Nurul M; Salma Zuratul F; Ulfa Mutiara Tanjung; Lina Novita (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to systematically synthesize empirical research findings addressing the application of Universal Design for Learning (UDL) in developing teaching materials for inclusive education, particularly at the elementary school level. The method used was a Systematic Literature Review (SLR) with reference to the PRISMA guidelines. Articles were collected from various scientific databases of national and international journals. A total of 25 empirical research articles published between 2009 and 2025 were analyzed. The study results indicate that the development of UDL-based teaching materials consistently has a positive impact on learning accessibility, active student participation, and student learning outcomes in inclusive classes. The most dominant UDL principles applied are multiple means of representation and engagement. However, research at the elementary school level and in the Indonesian context is still limited. These findings indicate the opportunity to develop contextual UDL-based teaching materials that are relevant to national curriculum policies as a direction for future research and practice in inclusive education.